Relação entre o alargamento do canal Uricurituba e as transformações na foz do rio Araguari (AP) no período de 2009 a 2023: uma análise por sensoriamento remoto - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
The Araguari River, the main watercourse of the largest hydrographic basin in the state of Amapá, has undergone significant morphological transformations in recent decades, particularly in its lower course, characterized by the progressive siltation of its mouth and by its connection with, and subsequent widening of, the Uricurituba Channel. This study aimed to analyze the relationship between these two processes using remote sensing and geoprocessing techniques. Landsat images from 2009 to 2023 were classified in QGIS software, and cross sectional measurements were performed along the channel. The results revealed a drastic reduction in the water surface area at the river mouth, from 86.22 km² in 2009 to 2.26 km² in 2023, accompanied by a significant increase in exposed soil, which reached 96.19 km² in the same period. In 2012, the Uricurituba Channel, in addition to connecting to the Araguari River, recorded progressive widening over the years, reaching more than 2 km in width in its lower section by 2023. Statistical analysis based on the Pearson correlation coefficient demonstrated a strong positive correlation (r between 0.80 and 0.95) between channel widening and the increase of exposed soil or siltation at the Araguari River mouth, and a strong negative correlation (r between –0.63 and –0.87) with the water surface area. These results highlight the direct connection between upstream fluvial processes and downstream environmental changes, emphasizing the role of geotechnologies in understanding and monitoring hydrosedimentary dynamics.
Keywords: Rio Araguari; Assoreamento; Canal Uricurituba; Sensoriamento remoto; Geoprocessamento; Correlação de Pearson; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA AMBIENTAL; ODS 6 – Água potável e saneamento; ODS 13 – Ação contra a mudança global do clima; ODS 15 – Vida terrestre